Teacher’s problems and solutions in implementing student-centered learning in SMAN Bali Mandara Singaraja - Putu Erna Adnyani; I Putu Ngurah Wage Myartawan; I Nyoman Pasek Hadi Saputra (Universitas Islam Malang, 2021)
This qualitative descriptive study aimed at analyzing teachers’ problems and solutions in implementing Student-centered Learning. This study involved an English teacher in SMA N Bali Mandara Singaraja. The instruments of this study consisted of voice recorder, field notes, interview guide, and researcher as the main instrument. The obtained data were analyzed using Miles and Huberman (1994) theory which consisted of data collection, data reduction, data display and conclusion drawing/verification. The results showed that the teacher's problems included problems caused by students, teacher, and facilities to support learning. The teacher’ solutions to solve the problems were by identifying the students' ability, motivating students personally, doing the class management well, using “stick talking” game to lead students to ask a question, instructed students to find more resources on the internet or library, giving a reward, instructed students to revise their planning when it was not meeting the minimum score before mobilizing them to the other group or permitting them to choose individual task based on their interest, grouping students evenly based on the identification result, scheduling and instructing them to do a discussion with their friend before consulting their project to the teacher and the last borrowing tools from the school facilities section and rotating the tool usage.Keywords: student-centered learning (SCL); teachers’ problem; teachers’ solution; 2013 curriculum